Employees’ perceptions and the relationship between human resource management and organizational performance: a conceptual view - Pombo, Gonçalo (2022)
The paper presents a review of the literature and advances a set of propositions concerning the employees’ perceptions on the relationship between human resource management and organizational performance. The study is aimed at filling the gap in the literature on the employees’ perception regarding human resource policies and the relationship to organizational performance. Social information processing theory is used to advance the insights on how employees’ performance about human resource policies may influence the organizational performance. The review indicated that there is a positive relationship between the employees’ perceptions of human resource policies and overall performance of a given organization. A positive perception of the implemented policies influences various individual outcomes such as commitment, engagement, and satisfaction, amongst others. Shared perceptions among the employees are also considered to have a considerable impact on the organizational performance. Nevertheless, there is a need for further research to explore the relationship between human resource management and organizational performance in more detail.